PREVENTIVE MAINTENANCE MESIN RE-WEAVING OMNI PLUS TC800 DI PT. XX - Sidiq Ruswanto; Septa Dwi Narastyana (Politeknik Negeri Jakarta, 2017)
ABSTRACTPT. XX is engaged in autoparts tire cords manufacturing industry for two-wheelers and four-wheelers that fit the fields of students. One of the machines contained in this PT. X is Re-Weaving. Re-Weaving machine works by separate fabric become yarns then weave again until become Geige fabric with other types. Problems experienced by the Re-Weaving machine at this time is the unavailability of maintenance schedule. Preventive Maintenance system is considered able to prevent the decline in production function due to Breakdown Maintenance. So to avoid Breakdown Maintenance and going Down Time, this machine needs maintenance system in the form of Preventive Maintenance. The author has the goal that maintenance actions on Re-Weaving machine can be done based on the appropriate maintenance schedule, maintenance process can run well. Determining maintenance schedules based Reliability Centered Maintenance (RCM) methods. Failure machine data from 2015 – 2017 conducted study into the causes of engine failure from five critical componentKeywords : Preventive Maintenance, Reliability Centered Maintenance, Scheduling Maintenance, Standard Operating Procedure.ABSTRAKPT. XX bergerak dalam bidang industri manufaktur kain penguat ban untuk roda dua dan roda empat yang sesuai dengan bidang mahasiswa. Salah satu mesin yang terdapat di PT. X ini yaitu Re-Weaving .Re-weaving merupakan proses pengayaman kembali dari geige fabric (gulungan kain) menjadi geige fabric dalam tipe lain. Permasalahan yang di alami oleh Re-Weaving saat ini adalah belum tersedianya jadwal pemeliharaan. Sistem perawatan berupa. Preventive Maintenance dianggap mampu mencegah penurunan fungsi produksi karena adanya Breakdown Maintenance. Maka untuk menghindari Breakdown Maintenance dan terjadi Down Time, mesin ini membutuhkan sistem perawatan berupa Preventive Maintenance. Penulis memiliki tujuan agar tindakan pemeliharaan pada mesin Re-Weaving dapat dilakukan berdasarkan jadwal pemeliharaan yang tepat, proses pemeliharaan dapat berjalan dengan baik. Penentuan jadwal pemeliharaan berdasarkan metode Reliability Centered Maintenance (RCM). Dari data kegagalan mesin tahun 2015 - 2017 dilakukan penelitian penyebab kegagalan mesin dari lima komponen kritisKata kunci : Preventive Maintenance, Reliability Centered Maintenance, Jadwal Pemeliharaan, Standard Operating Procedure.